With a Little Help from My (Random) Friends: Success and Failure in Post-Business School Entrepreneurship - Lerner, Josh; Malmendier, Ulrike (Review of Financial Studies, 2013)
How do individuals decide to become entrepreneurs and learn to make optimal entrepreneurial decisions? The concentration of entrepreneurs in regions such as Silicon Valley has stimulated research and policy interest into the influence of peers, but the causal effect is hard to identify empirically. We exploit the exogenous assignment of students into business-school sections to identify the causal effect of entrepreneurial peers. We show that, in contrast to prior findings, a higher share of entrepreneurial peers decreases, rather than increases, entrepreneurship. The decrease is driven by a reduction in unsuccessful entrepreneurial ventures; the effect on successful ventures is significantly more positive.